1989
DOI: 10.1093/oxfordjournals.eurheartj.a059473
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the optimal atrio-ventricular delay in DDD paced patients by impedance plethysmography

Abstract: The beneficial haemodynamic effects of sequential atrioventricular (AV) pacing have been clearly established and are dependent on the AV delay and pacing rate. However, the optimal AV delay is difficult to determine in each particular patient. We used a modified impedance plethysmographic method to assess variations in stroke volume for different AV delay and pacing rate settings. Impedance measurements showed a good correlation with CO2 rebreathing stroke volume measurements in VVI patients. Impedance variati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 0 publications
0
17
0
Order By: Relevance
“…Currently several methods are being used for optimization of AV-delay at various institutions including optimization according to the Ritter formula [28,29], use of bioimpedance [30], radionuclide ventriculography [31] or finger plethysmography [32], use of automated suggestion based on historical databases which take into account intrinsic AV-delay, QRS width and electrode positioning (ExpertEase, Guidant). Due to a lack of chronic data on the benefit of AV-delay optimization some centers simply program the device with a short AV-interval between 100 and 130 ms, although a recent study demonstrated a benefit of echocardiographically guided optimization of AV-delay [33].…”
Section: Comparison With Alternative Methods For Optimization Of Av-dmentioning
confidence: 99%
“…Currently several methods are being used for optimization of AV-delay at various institutions including optimization according to the Ritter formula [28,29], use of bioimpedance [30], radionuclide ventriculography [31] or finger plethysmography [32], use of automated suggestion based on historical databases which take into account intrinsic AV-delay, QRS width and electrode positioning (ExpertEase, Guidant). Due to a lack of chronic data on the benefit of AV-delay optimization some centers simply program the device with a short AV-interval between 100 and 130 ms, although a recent study demonstrated a benefit of echocardiographically guided optimization of AV-delay [33].…”
Section: Comparison With Alternative Methods For Optimization Of Av-dmentioning
confidence: 99%
“…The optimal AV delay is usually estimated by Doppler echocardiography, 16 radionuclide angiography 17 or plethysmographic impedance. 18 Our new method is easy and not time-consuming and so AV delay optimization can be easily repeated, making it a useful method for the follow-up of patients with congestive heart failure and a DDD-PM.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal AV interval in DDD pacing has been determined by many investigators with echocardiography, 7,10–12,16,17 peak endocardial acceleration, 18,19 and impedance cardiography 20,21 . In most of these studies, however, optimal AV interval was determined in patients with AV block.…”
Section: Discussionmentioning
confidence: 99%
“…Optimal AV interval in DDD pacing has been determined by many investigators with echocardiography, 7,10-12,16,17 peak endocardial acceleration, 18,19 and impedance cardiography. 20,21 In most of these studies, however, optimal AV interval was determined in patients with AV block. Ishikawa et al demonstrated that optimal AV interval could be predicted easily by a simple formula with pulsed Doppler echocardiography: slightly prolonged AV interval minus the interval between end of the A wave and the complete closure of mitral valve at the AV interval setting.…”
Section: Discussionmentioning
confidence: 99%